Transient receptor potential ankyrin-1 has a major role in mediating visceral pain in mice - Cattaruzza, Fiore (American Physiological Society, 2010)
The excitatory ion channel transient receptor potential ankyrin-1 (TRPA1) is prominently expressed by primary afferent neurons and is a mediator of inflammatory pain. Inflammatory agents can directly activate [e.g., hydroxynonenal (HNE), prostaglandin metabolites] or indirectly sensitize [e.g., agonists of protease-activated receptor (PAR(2))] TRPA1 to induce somatic pain and hyperalgesia. However, the contribution of TRPA1 to visceral pain is unknown. We investigated the role of TRPA1 in visceral hyperalgesia by measuring abdominal visceromotor responses (VMR) to colorectal distention (CRD) after intracolonic administration of TRPA1 agonists [mustard oil (MO), HNE], sensitizing agents [PAR(2) activating peptide (PAR(2)-AP)], and the inflammatory agent trinitrobenzene sulfonic acid (TNBS) in trpa1(+/+) and trpa1(−/−) mice. Sensory neurons innervating the colon, identified by retrograde tracing, coexpressed immunoreactive TRPA1, calcitonin gene-related peptide, and substance P, expressed TRPA1 mRNA and responded to MO with depolarizing currents. Intracolonic MO and HNE increased VMR to CRD and induced immunoreactive c-fos in spinal neurons in trpa1(+/+) but not in trpa1(−/−) mice. Intracolonic PAR(2)-AP induced mechanical hyperalgesia in trpa1(+/+) but not in trpa1(−/−) mice. TNBS-induced colitis increased in VMR to CRD and induced c-fos in spinal neurons in trpa1(+/+) but not in trpa1(−/−) mice. Thus TRPA1 is expressed by colonic primary afferent neurons. Direct activation of TRPA1 causes visceral hyperalgesia, and TRPA1 mediates PAR(2)-induced hyperalgesia. TRPA1 deletion markedly reduces colitis-induced mechanical hyperalgesia in the colon. Our results suggest that TRPA1 has a major role in visceral nociception and may be a therapeutic target for colonic inflammatory pain.